A state-of-the-art review and feasibility analysis of high altitude wind power in Northern Ireland. (February 2017) - Lunney, E.; Ban, M.; Duic, N.; Foley, A.
Abstract: In many countries wind energy has become an indispensable part of the electricity generation mix. The opportunity for ground based wind turbine systems are becoming more and more constrained due to limitations on turbine hub heights, blade lengths and location restrictions linked to environmental and permitting issues including special areas of conservation and social acceptance due to the visual and noise impacts. In the last decade there have been numerous proposals to harness high altitude winds, such as tethered kites, airfoils and dirigible based rotors. These technologies are designed to operate above the neutral atmospheric boundary layer of 1300 m, which are subject to more powerful and persistent winds thus generating much higher electricity capacities. This paper presents an in-depth review of the state-of-the-art of high altitude wind power, evaluates the technical and economic viability of deploying high altitude wind power as a resource in Northern Ireland and identifies the optimal locations through considering wind data and geographical constraints. The key findings show that the total viable area over Northern Ireland for high altitude wind harnessing devices is 5109.6 km 2, with an average wind power density of 1998 W/m 2 over a 20-year span, at a fixed altitude of 3000 m. An initial budget for a 2 MW pumping kite device indicated a total cost £1, 751, 402 thus proving to be economically viable with other conventional wind-harnessing devices.